The percentage of the individual's lifestyle and lifestyle contribution to heart attack for men aged 45-50 years (Journal of the College of Basic Education, 2022)
The introduction and its importance include the research on the importance of the style and lifestyle that the individual lives and its impact on the incidence of many diseases, some of which are serious, such as heart disease and atherosclerosis, which lead to the occurrence of a heart attack, myocardial infarction, and then death.